European Investment Advisory Hub Annual report 2019 - Investment Bank, European (2020)
This report illustrates how the European Investment Advisory Hub, a joint initiative with the European Commission, helps project promoters, the European Union, the European Investment Bank (EIB) and other financial institutions achieve their mission and get investment projects off the ground. This report provides a summary of the Advisory Hub's activities in 2019 and a number of case studies of investment projects supported by the Hub in the reporting year.